Study of Factors Inhibiting Digital Promotion in the Commercialization of BPR Sentral Arta Jaya KC Kraksaan Products - Adi Yasin Maulana Azis; Fahrudin (Majapahit Journal of Islamic Finance and Management, 2026)
The development of digital technology has encouraged the banking sector to utilize digital promotions as a marketing strategy to increase product commercialization. However, BPR Sentral Arta Jaya, Kraksaan Branch, has not yet implemented digital promotions and still relies on conventional promotions, which have the potential to leave the BPR behind other banks. This study aims to analyze the factors that hinder the implementation of digital promotions at BPR Sentral Arta Jaya, Kraksaan Branch. The study used a qualitative approach with a case study design. Data were obtained through interviews, observations, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that there are three main factors that hinder the implementation of digital promotions: regulations and policies from the head office that limit branch flexibility, limited human resource capabilities in the field of digital marketing, and minimal budget availability to support facilities, infrastructure, and competency development. This study concludes that the success of digital promotion implementation is not only determined by technology, but also by organizational support, human resource readiness, and adequate budget availability.